COMBATTING FRAUD IN STATE-OWNED ENTERPRISES USING BLOCKCHAIN AND IOT TECHNOLOGIES - M. Syahrudin; Sani Susanto (Universitas Airlangga, 2025)
Fraud in strategic sectors such as energy and finance, particularly within state-owned enterprises, remains a critical challenge to national economic integrity. Despite increased state revenues, the incidence of fraud continues to rise, highlighting the urgent need for robust technological interventions. This study aims to explore how Blockchain and Internet of Things (IoT) technologies have been utilized in anti-fraud systems over the past decade. Employing a Systematic Literature Review (SLR) approach guided by the PRISMA framework and conducted using the Watase Uake platform, this study analyzed 69 articles indexed in Scopus from 2015 to 2025. The analysis revealed a significant rise in research activity on this topic since 2019, peaking in 2022. The findings indicate that Blockchain’s decentralization and immutability, combined with IoT’s real-time monitoring capabilities, create a synergistic effect in enhancing fraud detection and prevention mechanisms. Empirical examples, such as fuel distribution frau d in Pertamina, illustrate how these technologies can reduce information asymmetry and improve audit quality. This study contributes to the literature by offering an integrated framework for leveraging emerging technologies in building transparent, secure, and efficient anti-fraud systems.